The characteristics of the newborn babies in Krosno (the podkarpackie voivodeship) born in 2011-2012 = Charakterystyka urodzeniowa noworodków krośnieńskich (województwo podkarpackie) urodzonych w latach 2011-2012 - Wandycz, Artur; Biczysko, Grażyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article aims to show how the weight and length of newborn babies depend on gestational age and mother's age. The study focused on the babies born in 2011-2012 in a hospital in Krosno (the Podkarpackie Voivodeship). Only live born children, born between the 38th and 42nd weeks of pregnancy, and with birth weight over 2500 g were taken into account. The results obtained allow stating that boys are on average heavier and longer than girls. The duration of pregnancy between the 38th and 42nd weeks is associated with an increase of birth weight and length of the body in the subsequent weeks of gestational age. In the case of boys, birth body weight and body length increase with mother`s age.
Keywords: noworodki; urodzeniowa długość ciała; urodzeniowa masa ciała; wiek płodowy; wiek matki; newborns; birth weight; birth body length; gestational age; maternal age